Digital information and communication technologies as a tool for the dissemination of science – an alternative in times of COVID-19 Pandemic (Research, Society and Development, 2022)
Due to the suspension of on-site classes in 2020, due to the COVID-19 pandemic, the use of Digital Information and Communication Technologies became essential for the continuity of teaching and learning. Considering this context, the Biodiversity Study Group and the Wild Animal Study Group of the Federal University of Piauí held 33 online events in the area of unique health, clinic, management and conservation of wild animals. This paper aims to report this experience and to describe the profile of participants interested in acquiring knowledge in these areas with the use of digital technologies. Through questionnaires answered during the events, it was possible to verify an audience of more than 4,000 people, the majority being higher education students (86.07%), aged between 18-25 years (83.44%) and belonging to courses in Veterinary Medicine (59.68%) and Biological Sciences (32.68%). The activities had subscribers from 8 countries and 278 institutions, mainly from the private network. We were able to demonstrate the benefit of using digital technology in continuing education for current or little-explored topics in social media or universities.